2009
DOI: 10.1111/j.1365-2311.2008.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body size and homing ability in the genus Osmia (Hymenoptera; Megachilidae)

Abstract: 1. The maximum homing ability of female bees, that is, their capacity to return to the nest after being displaced a certain distance, is considered to be an estimate of their maximum foraging distance.2. The present study provides data on homing ability and body weight for Osmia lignaria and combines them with data for five other congenerics, O. rufa , O. cornuta , O. pedicornis , O. cornifrons , and O. emarginata for analysis. These species are important pollinators of spring-flowering plants, and some have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 23 publications
5
44
0
Order By: Relevance
“…More elongated wings in larger species are traits that suggest a larger Xying range as has been reported in birds (Kaboli et al 2007); however, the results are far from conclusive in insects because positive relationships between body size and Xy range have been found in several bee groups (Abrol and Kapil 1994;Gathmann and Tscharntke 2002;Greenleaf et al 2007;Guédot et al 2009;van Nieuwstadt and Ruano Iraheta 1996), although no relationship has been reported in dragonXies (Johansson et al 2009), bumble bees (Knight et al 2005) and, signiWcantly, Neotropical social vespids (Raw 1998). In addition, Ennos (1989) in a theoretical study considering the Reynolds number values at which insects operate has shown that long slender wings might be less eYcient than moderately broad wings.…”
Section: Large Species and Body Weightmentioning
confidence: 81%
See 1 more Smart Citation
“…More elongated wings in larger species are traits that suggest a larger Xying range as has been reported in birds (Kaboli et al 2007); however, the results are far from conclusive in insects because positive relationships between body size and Xy range have been found in several bee groups (Abrol and Kapil 1994;Gathmann and Tscharntke 2002;Greenleaf et al 2007;Guédot et al 2009;van Nieuwstadt and Ruano Iraheta 1996), although no relationship has been reported in dragonXies (Johansson et al 2009), bumble bees (Knight et al 2005) and, signiWcantly, Neotropical social vespids (Raw 1998). In addition, Ennos (1989) in a theoretical study considering the Reynolds number values at which insects operate has shown that long slender wings might be less eYcient than moderately broad wings.…”
Section: Large Species and Body Weightmentioning
confidence: 81%
“…stated that "One of the challenges in developing a comprehensive theory of biological Xight is to understand how aerodynamic mechanisms change with body size"; thus, a complete analysis of the relationship between body size, wing shape and associated musculature may provide critical information regarding this subject (Dudley 2001;Guédot et al 2009;Aono et al 2008). Although comparative studies within Insecta have shown a general relationship between wing shape and body size, these studies have included species with very diVerent habits, evolutionary histories, behaviors and morphologies, such as the sphingid moth Manduca sexta (Linnaeus, 1763), the honey bee Apis mellifera Linnaeus, 1758, and the fruit Xy Drosophila melanogaster Meigen, 1830(Dudley 2001Sane 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Because many of the native pollinators nest along field edges (Ricketts et al 2008) we predicted that richness and abundance of bees would be greater near the forest edge as compared to field interiors. Because flight distance for many bees depends on body size (Araújo, Costa, Chaud-Netto, & Fowler 2004;Greenleaf, Williams, Winfree, & Kremen 2007;Guédot, Bosch, & Kemp 2009) we also predicted that body size of taxa, represented by measures of the intertegular span between wings (Cane 1987), would be correlated with distance from the forest edge. Finally, because of the presence of large numbers of honey bees in our fields, we did not expect to find a relationship between numbers of wild bees and the amount of pollen on stigmas.…”
Section: Introductionmentioning
confidence: 99%
“…Some species of solitary bee, e.g. Megachilinae spp., have been more extensively studied because of their importance for the spring pollination of fruit trees (Torchio, 1976;Bosch et al, 2006;Krunić & Stanisavljević, 2006;Guedot et al, 2009). Smaller solitary and social bee species have received much less attention, even though their species diversity is greater than larger bees, and are often in greater abundance (Westphal et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…On each day 30 traps were arranged in 6 transects with 5 sample points on vation or measurement. For example: adding artificial tube nesting sites (Tscharntke et al, 1998) using movable feeding stations (van Nieuwstadt & Rhoano Iraheta, 1996) or the homing of bees following translocation (Fabre, 1914;Gathmann & Tscharntke, 2002;Guedot et al, 2009). Furthermore simplifying assumptions have to be made about the activities and diversions of the bees as they fly between their foraging and nesting sites.…”
Section: Introductionmentioning
confidence: 99%